The Eco-Problems and Green Economy Development in Kazakhstan: An Analytical Survey - Onyusheva, Irina; Ushakov, Denis; Van, Hung Tran (International Journal of Energy Economics and Policy, 2018)
Nowadays the environmental issues are very urgent in both political and economic contexts as it is all about human ability to live in appropriate quality conditions, growth and develop sustainably. The ecological problems of Kazakhstan and ways of their solution are interrelated within this global task. The result of the expected Third Industrial Revolution in the world could be the development of the green economy in Kazakhstan. Among these principles is the transition to renewable sources of natural resources, the introduction of energy efficiency and others. Based on existing scientific and research background of the green economy it has been concluded the analysis of the current ecological situation in the Republic of Kazakhstan, where particularly all regions have been taken into consideration. It has been analyzed the contemporary state of the air, water and land pollution of the country. It has been defined main ecological problems having a great impact on the country’s eco-economic development. It has been also identified main issues of Green Economy concerning some difficulties that need emergent solving as well as future development prospects. The findings of the survey have proved that the political conception of Green Economy accepted by Kazakhstan will improve the eco-economic state of Kazakhstan and be able to lead the country on the high ranking economic positions. Keywords: Green economy, eco-economy, development, Kazakhstan. JEL Classifications: Q01, Q4, Q5, O1